Presence of unsaturated sphingomyelins and changes in their composition during the life cycle of the moth Manduca sexta - Abeytunga, D.T.U.; Glick, J.J.; Gibson, N.J.; Oland, L.A.; Somogyi, A.; Wysocki, V.H.; Plot, R. (My University, 2001)
NMR and electrospray ionization tandem mass spectrometry were used to show for the first time the presence of sphingomyelins in extracts of the tobacco hornworm Manduca sexta (Lepidoptera). The sphingosine in the ceramide was identified as tetradecasphing-4-enine, and the fatty acids were C18:0, C20:0, C22:0, and C24:0 (compound 1). Heterogeneity in the ceramide was observed in sphingomyelins from M. sexta. All of the sphingomyelins were associated with their doubly unsaturated sphingosine, tetradecasphing-4,6-dienine (compound 2), which contained the same set of fatty acids as compound 1 and represents a novel set of sphingomyelins not previously reported in Lepidoptera. Lipid rafts were isolated from brains of M. sexta, and the association of these novel sphingomyelins with rafts was confirmed. The existence of the additional double bond was also observed in ceramide and ceramide phosphoethanolamine isolated from M. sexta. The levels of the doubly unsaturated ceramide showed modest changes during metamorphosis of M. sexta. These results suggest that Manduca sphingomyelins may participate in the formation of lipid rafts, in keeping with their function in vertebrates
Keywords: ceramide; phosphoethanolamine; raft; apoptosis